2001
DOI: 10.1139/z00-223
|View full text |Cite
|
Sign up to set email alerts
|

Resighting and association patterns of bottlenose dolphins (Tursiops truncatus) in the Cedar Keys, Florida: insights into social organization

Abstract: Little is known about the social organization of bottlenose dolphins (Tursiops truncatus) inhabiting open estuarine systems. Our purpose was to identify and quantify the resightings of bottlenose dolphins and associations formed among them to provide insights into the social organization of the species in the open estuarine system of the Cedar Keys, Florida. We conducted monthly photographic-identification surveys from June 1996 through May 1997. We identified a total of 233 dolphins of which 217 (93%) were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 19 publications
2
78
0
1
Order By: Relevance
“…In the northeastern GoM, from St. Vincent Sound to Alligator Harbor, Tyson et al (2011) identified 2 year-round, parapatric communities of dolphins, differing in the degree of site fidelity of individuals (28.3 vs. 45.7% transients). Quintana-Rizzo & Wells (2001) examined resighting patterns for dolphins in the open estuarine system of Cedar Keys over a single year, and re ported that 19% of dolphins were observed over 5 mo or more, while others were seen less frequently.…”
Section: Discussionmentioning
confidence: 99%
“…In the northeastern GoM, from St. Vincent Sound to Alligator Harbor, Tyson et al (2011) identified 2 year-round, parapatric communities of dolphins, differing in the degree of site fidelity of individuals (28.3 vs. 45.7% transients). Quintana-Rizzo & Wells (2001) examined resighting patterns for dolphins in the open estuarine system of Cedar Keys over a single year, and re ported that 19% of dolphins were observed over 5 mo or more, while others were seen less frequently.…”
Section: Discussionmentioning
confidence: 99%
“…The individuals sighted were classified into four age categories based on their behavior and size estimates (BEARZI et al, 1997;SMUTS, 1998;CONNOR et al, 2000;MANN et al, 2000;QUINTANA-RIZZO;WELLS, 2001;CAMPBELL et al, 2002): (a) neonate -< 1/3 of adult size, presence of fetal folds, immature swimming, stereotyped surface respiration, frequent and non-coordinated head-butting against the water; (b) calf -1/2 of adult size, typical dislocation behind the dorsal fin of the presumed mother; (c) juvenile -2/3 of adult size; and (d) adultapproximately 3 m in length.…”
Section: Field Proceduresmentioning
confidence: 99%
“…Photographic data were also used to compute half-weight (i. e. controlled for sighting frequencies) coefficients of association (COA) for each dyad (pair of individuals; e. g. Smolker et al 1992;Bräger et al 1994;Félix 1997;Quintana-Rizzo and Wells 2001;Rogers et al 2004) using SOCPROG 2.4 (Whitehead 2009). COA values range from zero for dolphins that are never seen together, to one for a pair that is always seen together.…”
Section: Methodsmentioning
confidence: 99%
“…COA values range from zero for dolphins that are never seen together, to one for a pair that is always seen together. COA values were categorized as infrequent (0.0 -0.2), casual (0.2 -0.4), fair, (0.4 -0.6), moderate (0.6 -0.8) or strong (0.8 -1.0; Smolker et al 1992;Quintana-Rizzo and Wells 2001). Also, to prevent the occurrence of artificial dyads (i. e. individuals photographed together by chance due to our inclusive definition of group), a preferred/avoided partner assessment was developed through a permutation test Bejder et al 1998;Gero et al 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation